Mpasi Dan Cemilan Sehat Berbahan Dasar Lokal: Makanan Pendamping Bayi - Hastuty, Ade; Febiola, Andi; Wahyuddin, Wahyuddin (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
An Android-based application for making MPASI (complementary food for breast milk) and healthy snacks made from local ingredients is an innovative solution in increasing the accessibility and efficiency of providing optimal nutrition for toddlers. This research aims to develop an application prototype that provides recipe guides, nutritional calculators, and locally based educational training. The research method involves designing and testing applications with an iterative approach that involves users. The results show that this application helps users choose healthy local ingredients, prepare nutritious menus, and increase awareness of the importance of baby nutrition.